EFL Teachers’ Perceptions of Promoting 21st-Century Learning and Innovation Skills in Burundi Post-Basic Schools - Juvénal Habonimana; Marie Immaculée Ndayimirije; Emmanuel Barankanira (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
Today, global education seeks to equip students with the skills necessary to address complex challenges arising from a rapidly changing, competitive, and technology-driven world. Consequently, many countries have reformed their educational systems to meet the requirements of 21st-century pedagogy. In the field of English Language Teaching (ELT), teachers play a central role in implementing these pedagogical approaches. This study describes EFL teachers’ perceptions of promoting 21st-century learning and innovation skills among Level 2 learners in the Languages Track of post-basic schools in Burundi. A quantitative research design was employed, and data were collected from 17 teachers using a Likert-scale questionnaire. Descriptive statistical analyses were conducted using the Statistical Package for the Social Sciences (SPSS; Version 22) and R software (Version 4.1.2). The findings indicate that English teachers’ overall perceptions of promoting 21st-century learning and innovation skills were moderately positive, reflecting a limited level of engagement in teaching and assessing these skills. Such perceptions may negatively affect the quality of language education required for learners to meet the demands of contemporary living and working environments. The study provides valuable insights for educational stakeholders, highlighting the need for targeted support to develop learners’ 21st-century skills and competencies.